Forecasting of ionospheric vertical TEC 1-h ahead using a genetic algorithm and neural network. Issue 7 (1st April 2015) - Huang, Z.; Li, Q.B.; Yuan, H.
Highlights A BP neural network optimized by genetic algorithm is developed. The hybrid model can improve forecast results. Forecast results in the low-latitude region need to be improved.